PENGARUH PELATIHAN, DISIPLIN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KOPERASI KARYAWAN BANK MANDIRI SYARIAH (KOPKAR BSM) - Turmono Turmono; Muhammad Sendi Septian (IKOPIN, 2019)
One of the aspects possibly affecting an employee in achieving the work success is the work capability. This research is aimed to knowing whether or not there is significant influence between the variables of Training, Discipline and Compensation for Employee’s Performance. This research adopts the quantitative method by conducting the parametric statistical analysis in terms of multiple linier regression. The data used is primary data with 40 employee respondents which is obtained from the questioner of the employees of Koperasi Karyawan Bank Syariah Mandiri (KOPKAR BSM). The data analysis results with data processing auxiliary instrument of SPSS statistic version 23 for window indicate that Training does not significantly influence the Employee Performance in this matter is indicated by t test result significance value namely 0.214 > 0.05. Discipline significantly influences the Employee Performance. It is indicated by t test result significance value namely 0.012 < 0.05. Compensation significantly influences the Employee Performance, indicated by t test result significance value of 0.047 < 0.05. Meanwhile Training, Discipline and Compensation influence significantly the Employee Performance with F test significance value namely 0.000 < 0.05. The contribution of Training, Discipline and Compensation influence to the Employee Performance variable is 45.3% while the remaining 54.70% contains other factors affecting the Performance not researched in this research model.